The Role of the Montessori Method in Developing Cognitive Abilities from the Perspective of Kindergarten Supervisors - Hamida Bashir Ghaith (Journal of Scientific and Human Dimensions, 2026)
This study aims to investigate the role of the Montessori approach in developing the cognitive abilities of kindergarten children from the perspective of kindergarten supervisors, as well as to explore the reality of its implementation in kindergartens. It also seeks to examine supervisors’ perceptions regarding the contribution of Montessori activities to the development of children’s cognitive skills, such as attention and concentration, thinking and problem-solving, memory, and perception and understanding. Furthermore, the study identifies the main challenges facing the implementation of the Montessori approach in kindergarten settings. The study adopted the descriptive-analytical method. Data were collected through a questionnaire administered to a simple random sample of supervisors from 15 kindergartens in the university district surrounding the University of Tripoli, with a total of 36 participants representing the study population. The results revealed a high level of implementation of the Montessori approach in kindergartens, and that it significantly contributes to the development of various cognitive abilities in children. The findings also indicated the presence of several challenges hindering its effective implementation, including a lack of educational materials, insufficient training, high classroom density, and limited administrative support. In light of these findings, the study recommends providing a supportive environment for implementing the Montessori approach, offering training programs for teachers, and overcoming the obstacles that hinder its application.